Educação em valores morais no ensino fundamental : levantamento de experiências e intervenção com educadores - Couto, Leandra Lúcia Moraes (2019)
In this study, we dedicated ourselves to the theme of education in moral values, that is, practices that aim to constitute autonomous individuals, from the perspective of constructivist authors. The general objective of our research was to characterize education practices in moral values developed in municipal elementary schools, as well as to get to know the conceptions of educators regarding the aforementioned education, in order to verify the educational needs of the public at hand in this field and to provide them with moments of reflection and acquisition of knowledge and skills that are necessary to carry these practices out. Therefore, we developed three studies. In study 1, we applied mail and internet survey on educational experiences in moral values through a questionnaire sent to education professionals in Espírito Santo (ES). In the second study, we conducted semi-structured individual interviews with 14 educators from a municipal public primary school in Vitória, ES, seeking to verify their conceptions and judgments about education in moral values. Finally, in study 3 we developed an intervention with education professionals aiming to provide moments of reflection and learning about such education. The intervention was carried out in the same school of Study 2 and had the participation of 14 educators. Among the results of study 1, it is important to mention the following: we obtained 46 reports of experiences, from which we infer that there are few municipal elementary schools in the ES that work on the moral education of learners. Among the reports obtained, few deal with structured projects. Regarding the conceptions of professionals about moral value, ethical value and education in moral values (study 2), we found content that draws near relativistic positions. Most of the professionals said that the family is mainly responsible for the moral education of children and young people. In the schools where they worked, there was no specific project of education in moral values. Most participants stated that they did not feel safe or able to carry out practices with the issue on focus. Regarding study 3, we highlight the low involvement of professionals in reading the chosen material and the distraction during intervention. Nevertheless, participants gained a greater understanding of the school's role in the moral education of students and in the elaboration of education projects in moral values, among other aspects. Furthermore, most of the teachers mentioned that after the intervention they began to feel assured to work with moral education in the school context. We believe that expanding the quantity and quality of educational experiences in moral values in the school context presupposes that educators receive training that comprises reflection on their conceptions and practices and acquisition of theoretical and methodological knowledge on the field.